Solve −4(2x − 1) = −6(x + 2) − 2.


Question: Solve −4(2x − 1) = −6(x + 2) − 2

An equation can be defined as a mathematical statement consisting of an equal symbol between two algebraic expressions that have the same value

Answer: The value of x for the equation −4(2x − 1) = −6(x + 2) − 2 is 9

Let's solve the given equation −4(2x − 1) = −6(x + 2) − 2

Explanation:

−4(2x − 1) = −6(x + 2) − 2

=> -8x + 4 = -6x -12 - 2                  (By using distributive property)

=> -8x + 6x = -12 - 2 - 4                 (By combining like terms)

=> -2x = -18

=> x = 9                             

Thus, the value of x for the equation −4(2x − 1) = −6(x + 2) − 2 is 9